2013
DOI: 10.1021/nn305196q
|View full text |Cite
|
Sign up to set email alerts
|

In SituSynchrotron X-ray Fluorescence Mapping and Speciation of CeO2and ZnO Nanoparticles in Soil Cultivated Soybean (Glycine max)

Abstract: With the increased use of engineered nanomaterials such as ZnO and CeO₂ nanoparticles (NPs), these materials will inevitably be released into the environment, with unknown consequences. In addition, the potential storage of these NPs or their biotransformed products in edible/reproductive organs of crop plants can cause them to enter into the food chain and the next plant generation. Few reports thus far have addressed the entire life cycle of plants grown in NP-contaminated soil. Soybean ( Glycine max ) seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
219
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(237 citation statements)
references
References 41 publications
13
219
1
Order By: Relevance
“…Nodule content of ceria approached 11 mg/kg in some instances and electron microscopy confirmed the complete absence of symbiotic bacteria. Similarly, HernandezViezcas et al 67 used synchrotron µXRF and µXANES to observe nanoceria within soybean root nodules and pods, although up to 20% had been transformed from Ce(IV) to Ce(III).…”
Section: Soil Exposures In Plantsmentioning
confidence: 99%
“…Nodule content of ceria approached 11 mg/kg in some instances and electron microscopy confirmed the complete absence of symbiotic bacteria. Similarly, HernandezViezcas et al 67 used synchrotron µXRF and µXANES to observe nanoceria within soybean root nodules and pods, although up to 20% had been transformed from Ce(IV) to Ce(III).…”
Section: Soil Exposures In Plantsmentioning
confidence: 99%
“…fertilizers [2][3][4], antimicrobial agents [5][6][7], removal of contaminants [8][9][10] and clinical use [11][12][13][14][15]), as well as unintended exposure (e.g. contamination [16] and general uptake by all types of organisms [17][18][19][20]) has been analysed in a large body of work. These studies clearly point out that in fact NPs have an impact on the environment, whether intended or unintended.…”
Section: Introductionmentioning
confidence: 99%
“…While all Au remained as particles in plant shoots and 79% of Ce maintained the original CeO 2 coordination, CuO ENMs accumulation by Triticum aestivum (wheat) shoot were in particulate ((64±10)%) and complexed forms (Cu(I)-sulfur complexes ((36±10)%)). ZnO ENMs-exposed plants (Triticum aestivum, Glycine max) have Zn as Zn(II)-phosphate or Zn-citrate complexes; no elemental particles were observed (Lopez-Moreno et al, 2010a;Judy et al, 2011;Dimkpa et al, 2012;Hernandez-Viezcas et al, 2013). This cursory review of the literature clearly suggests that observed phytotoxicity likely result from a combination of ion-driven and sizedependent effects.…”
Section: Surface Contamination and Metal Speciationmentioning
confidence: 85%
“…Synchrotron-based microfocused X-rayfluorescence (μ-SXRF) with microX-ray absorption near-edge structure (μ-XANES) or microXray diffraction (μ-XRD) are currently the most powerful set of techniques used for a complete characterization of biological samples. Among the set of techniques, μ-SXRF is very useful, allowing in situ mapping of nanoparticles with high sensitivity, negligible sample damage, and enable tuning of the incident energy as desired (Ma et al, 2011;Majumdar et al, 2012;Hernandez-Viezcas et al, 2013;Hummer and Rompel, 2013). Other promising advances include single particle inductively coupled plasma-mass spectrometry (spICP-MS), solid sampling highresolution-continuum source atomic absorption spectrometry (HR-CS AAS) and two-photon excitation microscopy (TPEM) (Wild and Jones, 2009;Feichtmeier and Leopold, 2013;Gray et al, 2013).…”
Section: Perspectives and Research Prioritiesmentioning
confidence: 99%